Rzeź Ormian w dyskursie izraelskim - Budzik, Jagoda (Slavia Occidentalis, 2015)
The article attempts to give a brief overview of the history of Israeli discourse on the Armenian Genocide, which still has not been officially recognised by the State of Israel. The main objective of the paper is to point out the key events and attitudes taken as part of the Israeli discourse that are – directly and indirectly – responsible for this situation. The problem is analysed in two major contexts – namely those of the official, Israeli Holocaust discourse and the foreign politics of the state, including the influence these two spheres had on the Armenian Genocide’s official status in the Israeli collective memory.